α - Glucosidase inhibitory and antioxidant activities of entada spiralis ridl. (Sintok) stem bark extracts - Opeyemi Roheem, Fatimah; Mat So'ad, Siti Zaiton; Ahmed, Qamar Uddin; Mohd Hassan, Norazian (Universiti Putra Malaysia, 2019)
Entada spiralis Ridl. (Leguminosae), locally known as “Sintok” or “Beluru” is a tropical woody climber that grows widely in Malaysia. It is a valuable and well known plant in herbal medicine due to its various traditional and medicinal applications. Crude extracts were obtained from the stem bark by using petroleum ether, chloroform and methanol as extracting solvents and were then biossayed for their biological potential. The antioxidant and alpha-glucosidase inhibitory activities of the extracts were assessed by using DPPH, ABTS, β-carotene and α-glucosidase inhibitory methods respectively. Qualitative analysis showed the presence of most of the phytochemicals in methanol extract; however, chloroform and petroleum ether extracts contained terpenoid and tannins as their major phytoconstituents respectively. Methanol extract contained the highest amount of total phenolics (42.5 ± 15.85 µg/ml) and flavonoids (28.94 ± 2.93 µg/ml), and showed the most potent α-glucosidase inhibitory activity with IC50 value of 20.67 µg/ml. The same methanol extract exhibited highest β-carotene bleaching inhibition (27% at 1 mg/ml), while methanol and chloroform extracts exhibited good radical scavenging activities dose dependently (IC50 37.29 ± 0.05, 90.84 ± 3.12 µg/ml respectively) against ABTS and DPPH radicals. Bioassay-guided silica gel column chromatography purification of the most active methanol extract afforded 3,4′,5,7- tetrahydroxy flavone (6 mg). The compound displayed promising inhibitory activity against free radicals as well as α-glucosidase enzyme. These results further suggest the traditional medicinal uses of E. spiralis Ridl. stem bark as a therapeutic agent against hyperglycemia.